2022
DOI: 10.3389/fpsyg.2022.766036
|View full text |Cite
|
Sign up to set email alerts
|

Caring for Psychological Distress of Patients With COVID-19: A Mixed-Method Cross-Sectional Study

Abstract: IntroductionThe 2019–2020 pandemic COVID-19 has become a global health crisis. While many recent studies on COVID-19 pandemic have focused on disease epidemiology and psychological status of patients, few have explored the multi-facet influential factors or combined perspectives from both the patients and healthcare workers. The purposes of this study were to: analyze the influencing factors of psychological distress of COVID-19 patients; and describe the experience of healthcare workers relieving psychologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Te results examine comprehensive care including diet, exercise, yoga, music, constructive interactions, including reading or playing with patients, and herbal and traditional remedies showed that the integration of new treatments and the provision of comprehensive care significantly increase the quality of care and reduces the negative aspect of the psychological dimension of isolation in patients [26]. Te results on the actions of formal caregivers for patients with COVID-19 also showed that the most important thing to deal with patient's psychological distress is to meet the patient's needs as much as possible and to promote the emotional connection between patients and caregivers and their families and providing ways to divert attention such as watching TV and listening to music [27]. In the present study, caregivers sacrifced their time, energy, fnancial resources, relationships, and feelings for others to care for their patients, consciously and responsibly, regardless of the consequences of 24-hour care.…”
Section: Discussionmentioning
confidence: 95%
“…Te results examine comprehensive care including diet, exercise, yoga, music, constructive interactions, including reading or playing with patients, and herbal and traditional remedies showed that the integration of new treatments and the provision of comprehensive care significantly increase the quality of care and reduces the negative aspect of the psychological dimension of isolation in patients [26]. Te results on the actions of formal caregivers for patients with COVID-19 also showed that the most important thing to deal with patient's psychological distress is to meet the patient's needs as much as possible and to promote the emotional connection between patients and caregivers and their families and providing ways to divert attention such as watching TV and listening to music [27]. In the present study, caregivers sacrifced their time, energy, fnancial resources, relationships, and feelings for others to care for their patients, consciously and responsibly, regardless of the consequences of 24-hour care.…”
Section: Discussionmentioning
confidence: 95%
“…Common intervention methods are recommended that combine psychological expertise and the characteristics of ID. Policymakers should establish a favorable environment to improve doctor-patient interactions and develop multi-dimensional social support to positively impact medical staff motivation ( Li et al, 2022 ). Administrators may help lead cognitive assessments by conducting group counseling and psychology lectures ( Bao et al, 2020 ; Wang et al, 2021 ; Wan et al, 2022 ), implementing cognitive behavioral and organizational behavioral treatments focused on mindfulness ( Hammer et al, 2015 ; David et al, 2018 ; Harolds, 2020a ; Naser et al, 2021 ), and assisting employees to keep a healthy work-life balance to improve their work concentration.…”
Section: Discussionmentioning
confidence: 99%
“…In Thailand, the number of male patients was higher than female [ 9 ]. The 25.7% of patients with COVID-19 still suffered from psychological distress, which should receive timely attention from healthcare workers, and the severity of the disease and disease uncertainty has a significant impact on distress [ 10 ]. A systematic review and meta-analysis reported that the global prevalence estimate was 28% for depression, 26.9% for anxiety, 24.1% for post-traumatic stress symptoms, 36.5% for stress, 50% for psychological distress, and 27.6% for sleep problems [ 11 ].…”
Section: Introductionmentioning
confidence: 99%